Analysis of Students' Science Process Skills Profile: Case Study in Pekanbaru - Jannah, M.; Zulirfan, Z.; Suzanti, F. (Universitas Negeri Yogyakarta, 2024)
The skills of the science process are crucial in science learning, yet they have not been fully maximized in science learning activities. The research aimed to analyze the profile of students' science process skills in Pekanbaru. The study used a descriptive method with a survey technique of students in class VII of SMPN 23 Pekanbaru for the 2023/2024 academic year. The sample was selected using a simple random sampling technique of 70 students, consisting of 33 students from VII Hang Tuah and 37 students from VII Hang Jebat. The instrument used a sheet of science process skills test consisting of 10 multiple-choice questions covering indicators observing, classifying, measuring and using numbers, inferring, communicating, formulating problems, formulating hypotheses, controlling variables, planning experiments, and interpreting data. The data collection technique involved distributing the science process skills test to students. The data analysis technique was done quantitatively by calculating the percentage score of students' science process skills per indicator based on students' test answers. The results showed that the percentage of students' science process skills overall is 54%, categorized as sufficient. The highest percentage is in the observation skill at 91%, while the lowest percentage is in the variable control skill at 10%. The poor science process skills are communication, variable control, experimental planning, and data interpretation. The research recommends further research as an initial stage in